The Spirit of Tolerance in Determining the Time of Dawn According to Indonesian Classical Scholars in Malay-Nusantara - Qorib, Muhammad; Juli Rakhmadi, Arwin (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study traces the spirit of tolerance of 5 Malay-Nusantara scholars about conception or early standards of dawn (Subuh). The five figures are Ahmad Khatib Minangkabau (d. 1334 H/1915 AD), Muhammad Mukhtar bin 'Atharid Bogor (d. 1349 H/1930 AD), Hasan bin Yahya Jambi (d. 1940 AD), and Muhammad Thahir Jalaluddin (d. 1376 H/1956 AD). Of the 5 figures, four of them set the standard of the beginning of Subuh time 19 degrees, while one figure namely Sheikh Muhammad Thahir Jalaluddin set 20 degrees. This 20-degree standard is commonly used by Muslims in the Southeast Asian region today. Eventhough they disagreed in some aspects, but they aprreciated the different methods they used, but they had the same goal